(untitled) (Caligrama: Revista de Estudos Românicos, 2020)
Resumo: Este artigo visa a fazer uma análise exploratória sobre a adaptação de Cahier d’un retour au pays natal (1939), texto de Aimée Césaire (1913-2008), para sua versão audiovisual homônima (2008) realizada por Philippe Bérenger (1960-). Para isso, primeiro, faz-se uma reflexão sobre os elos entre literatura e cinema e, depois, uma análise em cotejo das duas obras. Exploram-se os vínculos com os movimentos da Negritude e do Surrealismo, e com a pouca percorrida trilha das adaptações fílmicas de poemas. Em suma, esta é uma contribuição para os estudos literários do cinema e para os estudos de literatura de expressão francesa negra no Brasil. Palavras-chave: Aimé Césaire, Philippe Bérenger, negritude, poema, filme. Abstract: This article aims at carrying out an exploratory analysis of the adaptation of Cahier d’un retour au pays natal (1939), text written by Aimée Césaire (1913-2008), into the homonymous feature film (2008) directed by Philippe Bérenger (1960-). In order to do so, it first addresses the links between literature and cinema, and then analyses and compares the two pieces. We have also explored the connection to both the Negritude and Surrealistic movements, as well as the lack of film adaptations of poems. Therefore, this is a contribution to literary studies of cinema and to studies of francophone African diaspora literature in Brazil. Keywords: Aimé Césaire, Philippe Bérenger, negritude, poem, film.